Sharia mortgage in Indonesia: A critical inquiry into regulatory adequacy, contractual integrity, and market transformation - Cecep Bryan Firdaus (PRIVIETLAB, 2026)
This opinion paper critically examines the structural and regulatory architecture of Sharia-compliant mortgage financing, Kredit Pemilikan Rumah Syariah (KPR Syariah), in Indonesia, with particular attention to the normative tensions between classical Islamic jurisprudence and contemporary financial engineering. Drawing on established scholarship in Islamic finance, Indonesian positive law, and institutional economics, this study argues that the existing framework, while formally compliant with Fatwa Dewan Syariah Nasional—Majelis Ulama Indonesia, exhibits persistent ambiguities in contractual taxonomy, inadequate consumer protection architecture, and insufficient harmonization with the broader macroprudential objectives of Bank Indonesia and Otoritas Jasa Keuangan (OJK). This study further contends that the dominant murabahah-based KPR model, despite its widespread adoption, raises unresolved questions regarding risk distribution, profit margin transparency, and the authentic transfer of maqasid al-shari'ah principles into product design to be implemented. The analysis concludes with a normative agenda for reform oriented toward contractual fidelity, regulatory convergence, and genuine financial inclusion.